Quality of TEC Estimated with Mod Ion Using GPS and GLONASS Data - Camargo, Paulo de Oliveira [UNESP] (Hindawi Publishing Corporation, 2009)
One of the largest sources of error in positioning and navigation with GNSS is the ionosphere, and the associated error is directly proportional to the TEC and inversely proportional to the square of the signal frequency that propagates through the ionosphere. The equatorial region, especially in Brazil, is where the highest spatial and temporal value variations of the TEC are seen, and where these various features of the ionosphere, such as the equatorial anomaly and scintillation, can be found. Thus, the development and assessments of ionospheric models are important. In this paper, the quality of the TEC was evaluated, as well as the systematic error in the L1 carrier and the inter-frequency biases of satellites and receivers estimated with the Mod Ion, observable from GPS and integration with the GLONASS, collected with dual frequency receivers. Copyright (C) 2009 Paulo de Oliveira Camargo.